2021
DOI: 10.1038/s41467-020-20643-w
|View full text |Cite
|
Sign up to set email alerts
|

Nonpolarizing oxygen-redox capacity without O-O dimerization in Na2Mn3O7

Abstract: Reversibility of an electrode reaction is important for energy-efficient rechargeable batteries with a long battery life. Additional oxygen-redox reactions have become an intensive area of research to achieve a larger specific capacity of the positive electrode materials. However, most oxygen-redox electrodes exhibit a large voltage hysteresis >0.5 V upon charge/discharge, and hence possess unacceptably poor energy efficiency. The hysteresis is thought to originate from the formation of peroxide-like O22− d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
86
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(96 citation statements)
references
References 63 publications
(79 reference statements)
1
86
0
Order By: Relevance
“…Specifically, the oxidation products of the lattice oxygen in LSLR project more oxygen anions with an electron hole than LR. In a latest study, this effect was also achieved in a cathode material for sodium-ion batteries 37 . The underlying fine structure could be revealed by the vibration near the elastic peak at 0.1–0.9 eV (Fig.…”
Section: Resultsmentioning
confidence: 87%
“…Specifically, the oxidation products of the lattice oxygen in LSLR project more oxygen anions with an electron hole than LR. In a latest study, this effect was also achieved in a cathode material for sodium-ion batteries 37 . The underlying fine structure could be revealed by the vibration near the elastic peak at 0.1–0.9 eV (Fig.…”
Section: Resultsmentioning
confidence: 87%
“…In a recent work, Tsuchimoto et al confirmed a unique behavior of O in Na 2 Mn 3 O 7 using DFT calculations and magnetic and spectroscopic measurements (Figure 6(f)) [78]. The existence of thermodynamically favorable O −• over the peroxide-like O 2 2− dimers was predicted by computations and showed that hole stabilization occurred through a (σ + π) multiorbital Mn-O bond.…”
Section: P3-type Layered Compounds Na X [A Y Mnmentioning
confidence: 85%
“…Despite the promising low-voltage hysteresis and high capacity, Na 2 Mn 3 O 7 still suffers from degradation during cycling. Furthermore, the mechanism of the anion redox reaction with such a small hysteresis is still under debate [78,79].…”
Section: Sodium-deficient Layered Structuresmentioning
confidence: 99%
See 1 more Smart Citation
“…After the 1 st cycle, the charge starts with a decrease in RCT which matches well the initial voltage slope between 1.5 and 1.9 V vs. LiIn:In, followed by a constant and lowest value of RCT corresponding to the plateau around 2 V. Thus, RCT displays a strong asymmetry between charge and discharge, and its variations appear to match well the voltage variations of LTFS. The strong asymmetry suggests that it might be related with the differing reaction pathways between charge and discharge for processes owing to the anionic redox process pertaining to the Li-rich layered sulphide LTFS as well documented 26,27 .…”
Section: Resultsmentioning
confidence: 99%